The Effect of Critical Work Factors on Employee Job Satisfaction and Motivation in Nepalese Commercial Banks - Dhakal, Sabina (Nepalese Journal of Management, 2024)
This study examines the effect of critical work factors on job motivation and satisfaction in Nepalese commercial banks. Employee job satisfaction and job motivation are selected as the dependent variables. Likewise, supervision, promotion, job stress, salary, working environment and co-worker relation are selected as the independent variables. The primary source of data is used to assess the opinions of the respondents regarding compensation and reward system in Nepalese commercial banks. The study is based on primary data with 150 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and impact of critical work factors on employee job motivation and satisfaction in Nepalese commercial banks. The study showed that supervision has a positive impact on employee job satisfaction and job motivation indicating that better supervision of employee performance leads to increase in level of employee job satisfaction and job motivation. Similarly, promotion has a positive impact on employee job satisfaction and job motivation. It means that fair promotion practices in the organization leads to increase in employee job satisfaction and job motivation. Furthermore, the result also shows that salary has a positive impact on employee job satisfaction and job motivation. It means that increase in salary leads to increase in the level of employee job satisfaction and job motivation. Likewise, working environment has a positive impact on employee job satisfaction and job motivation. It indicates that better working environment leads to increase in the level of employee job satisfaction and job motivation. Moreover, co-worker relation has a positive impact on employee job satisfaction and job motivation. It means that good relationship among the employees leads to increase in employee job satisfaction and job motivation. However, job stress has a negative impact on employee job satisfaction and job motivation. It means that increase in job stress leads to decrease in the level of employee job satisfaction and job motivation.